Kajian Antropometri & Ergonomi Desain Mebel Pendidikan Anak Usia Dini 3-4 Tahun di Siwalankerto - Jennie Hasimjaya (Intra, 2017)
The furniture for early childhood in Siwalankerto does not suitable with the anthropometry and not ergonomic when used for children with the age of 3-4 years old that have more activities which involved furniture. This experiment must be done with the study of anthropometry and ergonomically suitable for aerly childhood with the age of 3-4 years old in Siwalankerto. This research was ained to get the exact athropometry for 3-4 years old children and to decide the furniture size ergonomically, so that it would be comfortable and reduce the abnormalities caused by the failure in furniture dimension. This research used quantitative with the survey explanation format. The result of this experiment was the dimension of early childhood in Siwalankerto with the age of 3-4 years old and the fit dimension of furniture based on the anthropometry.